Lincoln's Speeches Reconsidered - Briggs, John Channing (Johns Hopkins University Press, 2020)
Originally published in 2005. Throughout the fractious years of the mid-nineteenth century, Abraham Lincoln's speeches imparted reason and guidance to a troubled nation. Lincoln's words were never universally praised. But they resonated with fellow legislators and the public, especially when he spoke on such volatile subjects as mob rule, temperance, the Mexican War, slavery and its expansion, and the justice of a war for freedom and union.In this close examination, John Channing Briggs reveals how the process of studying, writing, and delivering speeches helped Lincoln develop the ideas with which he would so profoundly change history. Briggs follows Lincoln's thought process through a careful chronological reading of his oratory, ranging from Lincoln's 1838 speech to the Springfield Lyceum to his second inaugural address.Recalling David Herbert Donald's celebrated revisionist essays (Lincoln Reconsidered, 1947), Briggs's study provides students of Lincoln with new insight into his words, intentions, and image.